A novel MEMS actuator with large lateral stroke driven by Lorentz force. (22nd January 2015) - Lv, Xingdong; Wei, Weiwei; Mao, Xu; Yang, Jinling; Yang, Fuhua
Abstract: This paper presents a novel MEMS actuator driven by Lorentz force. The actuator has a structure of folded beams, which is favorable for a large lateral stroke. A displacement of more than 47 μ m was achieved with a magnetic field of 0.3 T and a driving current of 8 mA. The actuator can generate a large displacement under a low driving voltage and can easily be integrated with CMOS circuits. Lorentz force is proportional to the magnetic field and the driving current, which results in a linear dependence of the lateral displacement on the driving current.